A Globally Convergent Hybrid Conjugate Gradient Method and Its Numerical Behaviors. (22nd April 2013) - Huang, Yuan-Yuan; Liu, San-Yang; Du, Xue-Wu; Dong, Xiao-Liang
Abstract : We consider a hybrid Dai-Yuan conjugate gradient method. We confirm that its numerical performance can be improved provided that this method uses a practical steplength rule developed by Dong, and the associated convergence is analyzed as well.